Nonsustained Ventricular Tachycardia in Heart Failure - Al-Hadithi, Mutaz Fawzi Hussain; Al-Dulaimi, Khalid Maseer (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Heart failure is a common clinical syndrome with a high morbidity and mortality, despite advances in medical treatment. Death from dangerous ventricular arrhythmias is frequently implicated. Patients, materials & methods: Eighty patients with heart failure (HF) (fitting the criteria of heart failure) who were admitted to the medical city teaching hospital during a period of 8 months, were studied for incidence of nonsustained ventricular tachycardia (N.S.V.T.) (detected by Holter monitoring) and its association with the severity of left ventricular dysfunction (measured by ejection fraction), ventricular size (measured by left ventricular end diastolic dimension), and other factors . Results: It was found that out of 80 patients with H.F, 20 patients (25%) have N.S.V.T. N.S.V.T was found to be significantly associated with the severity of H.F. and left ventricular dimension. The arrhythmia was found to be strongly related with hypokalemia. The incidence of N.S.V.T. is less in patients receiving beta-blockers in their treatment regimen. Conclusion: Nonsustained ventricular tachycardia is a common finding in heart failure and is related to the severity of heart failure and other factors related to the disease and its treatment.